Discusiones acerca de la educación financiera en las escuelas secundarias de la Ciudad de Buenos Aires - Jorge Damian Lo Cascio (Clio y Asociados, 2022)
In January 2022, Buenos Aires City´s Government announces the implementation of a financial education course for students at the last year of the secondary schools. This paper contributes to the discussion on the governmental proposal with the intention of framing the debate from a perspective of the didactics of the economy, therefore, it seeks to answer why and what for financial literacy?, and what kind of financial education? To answer the questions, a literary review on financial education in the international arena, focusing on the recommendations of the OECD, the PISA tests, and the Spanish experience. The last section seeks to collect lessons that may be interesting for the Buenos Aires City.